Isak 35 Practice on Financial Statements of Organizationsnon-Profit at the Cathedral Church St. Theresia Lisieux Sibolga - Sahala Purba; Calista (MultiTech Publisher, 2023)
Cathedral Church of St. Theresia Lisieux and other non-profit organizations rely on the preparation and delivery of financial reports, so professional groups that provide support to Indonesian Accountants (IAI) must provide new interpretations of financial reporting norms. PSAK 1 Amendment to the Presentation of Financial Reports IAI publishes an explanation of Accounting Standards Number 35 (ISAK 35) to improve understanding of the financial reports prepared and submitted. Cathedral Church of St. Theresia Lisieux would benefit from this. in obtaining external financial support. The purpose of this research is to compare the financial statements of St. Theresia Lisieux's financial reports comply with the ISAK 35 financial reporting framework. This research uses qualitative technical methods; Practice at Cathedral Church of St. Theresia Lisieux Descriptive analysis was used to compare Theresa Lisieux's theory and ISAK 35. Data for this research was collected through observation. Financial report of St. Cathedral Church Theresia Lisieux pointed out that the church has not yet developed its financial reporting mechanism in line with current requirements, especially ISAK 35, because the church only covers income and expenditure reports